Human CD4+ T cells are predominantly distributed among six phenotypically and functionally distinct subsets. - Amyes, E; Mcmichael, A; Callan, M (2005)
Human T cells are heterogeneous, varying in terms of their phenotype, functional capabilities, and history of Ag encounter. The derivation of a functionally relevant model for classifying CD4+ T cells has been hampered by limitations on the numbers of parameters that may be measured using classical four-color flow cytometry. In this study we have taken advantage of the introduction of reagents for five-color flow cytometry to develop a detailed, functionally meaningful scheme for classifying human CD4+ T cells. We show that CD4+ T cells are predominantly distributed among six of eight possible compartments, identified by the expression of CCR7, CD45RA, and CD28. We demonstrate novel phenotypic and functional correlates that justify the choice of these three molecules to define CD4+ T cell compartments. We note that CD4+ T cells with different Ag specificities are distributed differently among the six described subsets. On the basis of these results, we propose a cross-sectional model for classification of peripheral CD4+ T cells. Knowledge of where T cells lie on this model informs about their functional capacity and can reflect their history of Ag exposure.